Consumer Awareness and Acceptance of Aquaculture Practices and Products in Penang, Malaysia - See, Too Kay Leng; Chan, Ngai Weng; Tan, Mou Leong; Seow, Ta Wee; Samat, Narimah (European Publisher, 2019)
High demand of seafood products combined with over-harvesting of wild catch aquatic products have elevated aquaculture as the alternative way to strike a balance between seafood product supply and demand. However, uncontrolled aquaculture activities are found to affect the environment negatively as well as the health of consumers. Better awareness and understanding can regulate aquaculture practices and bring about environmental health through consumers’ pressure on the aquaculture production system. This study aimed to identify consumers’ perception on aquaculture industry, to study consumers’ awareness on sustainability of aquaculture practice and also to find ways to increase consumers’ awareness and acceptance of sustainable aquaculture practice and its products. A mixed research method was used in this study combining quantitative questionnaire survey of respondents who bought aquaculture products at wet markets in Penang, and qualitative in-depth focus group discussions (FGDs) with a number of selected respondents. Research findings show that most of the respondents are aware that aquaculture might give lots of negative effects to human health and the environment but, they still chose to buy aquaculture products due to cheaper price than wild catch seafood products. Hence, from the findings, it is clear that even though people have awareness, they have little choice but to accept the quality of aquaculture products. However, the results also show that enhancing consumer awareness and understanding empowers consumers to put pressures on producers paving the way towards sustainable aquaculture and greater acceptance of aquaculture practices and products.